2004
DOI: 10.1023/b:flui.0000030302.15633.26
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Hypersonic Shock Layer on a Flat Plate

Abstract: Stability of a hypersonic shock layer on a flat plate is examined with allowance for disturbances conditions on the shock wave within the framework of the linear stability theory. The characteristics of the main flow are calculated on the basis of the Full Viscous Shock Layer model. Conditions for velocity, pressure, and temperature perturbations are derived from steady Rankine-Hugoniot relation on the shock wave. These conditions are used as boundary conditions on the shock wave for linear stability equations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This means that vortex disturbances arise in the shock layer. Near the leading edge of the flat plate, the phase velocities obtained by the linear stability theory [4] are significantly different from the DNS data. A possible reason is that the linear stability theory [3,4] ignores nonparallelism of the mean flow, which is fairly noticeable in the vicinity of the leading edge.…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…This means that vortex disturbances arise in the shock layer. Near the leading edge of the flat plate, the phase velocities obtained by the linear stability theory [4] are significantly different from the DNS data. A possible reason is that the linear stability theory [3,4] ignores nonparallelism of the mean flow, which is fairly noticeable in the vicinity of the leading edge.…”
mentioning
confidence: 56%
“…It is seen in Fig. 1 that the DNS results for the slow mode are in good agreement [3,4] and direct numerical simulations, respectively; curves 1 and 2 refer to the slow and fast modes, respectively; the points are the experimental data [9].…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…In this case, it is necessary to take into account the influence of the shock wave and viscous-inviscid interaction on stability characteristics. The boundary conditions for disturbances on the shock wave were derived from the linearized Rankine-Hugoniot conditions (Chang, Malik & Hussaini 1990;Maslov et al 2004a;Maslov, Poplavskaya & Smorodsky 2004b). It was demonstrated that reflection of disturbances from the shock wave results in branching of the solutions of the linear stability problem; i.e.…”
Section: Introductionmentioning
confidence: 99%